Perlindungan dan Kedudukan Anak di luar Nikah Perspektif Fikih - Kadafi, Muh.; Shuhufi, Muhammad (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This article investigates efforts to protect children out of wedlock from the perspective of Islamic jurisprudence. In modern society, children born from extramarital relationships often face stigmatization and social risks that have the potential to harm their development. The fiqh perspective offers a rich view of moral and legal principles that can guide in understanding and overcoming these challenges. This article's analysis includes an understanding of Islamic law regarding marriage, the role of parental responsibility, and children's rights in aunconventional family context. The discussion also involved concepts such as marriage inheritance and social responsibility, as well as how to implement them in safeguarding the rights and welfare of children outside of marriage. Through a deeper understanding of the fiqh perspective, this article aims to identify value-based and ethical solutions to the problem of protecting children outside of marriage. This research is library research by examining written sources regarding efforts to protect children outside of marriage. The data collection method was carried out by obtaining primary data and secondary data, including the Koran, Hadith, Islamic jurisprudence books and journals as well as statutory regulations relating to the protection of children outside of marriage..